Opportunities and challenges in valorizing pulp and paper sludge for biogas production via anaerobic digestion: a review - Erfan Hosseini; Selen Cremaschi; Zhihua Jiang (Sustainability Science and Technology)
The integration of anaerobic digestion (AD) into pulp and paper mill operations presents a sustainable pathway for managing pulp and paper mill sludge (PPMS), a significant waste stream rich in organic matter. However, the process is constrained by the recalcitrant nature of lignocellulosic biomass, nitrogen deficiency, and low buffering capacity—factors that contribute to reduced methane yields and economic infeasibility. This review critically examines over 200 studies to identify key bottlenecks in the AD of PPMS. It evaluates emerging strategies to enhance biodegradability and economic feasibility, including alkaline pretreatment with green liquor dregs, combining primary sludge and secondary sludge, co-digestion with rejected fibers and nutrient-rich substrates, sequential H _2 and CH _4 production, and biochar addition. The paper also discusses the role of mechanistic and data-driven modeling in optimizing the AD of PPMS and reviews existing techno-economic analysis and life cycle assessment studies documented in the literature. These insights provide a valuable foundation for further research and supporting the practical implementation of AD within the pulp and paper industry.